Investigating the Influence of Human-AI Collaboration on Electronic Word of Mouth Through Customer Satisfaction in Event Services - Mark Joseph B. Marquez; Julien Albert Andal; Gabriel Molina; Maria Bianca Oliveros; Jayvie O. Guballo (International Journal for Applied Information Management, 2026)
High-touch events emphasize direct artist–fan interaction and have become an important driver of engagement and economic activity in the entertainment industry. However, limited research has examined how service quality in such events influences customer satisfaction and electronic word-of-mouth (e-WOM), particularly in the Philippine context. This study aims to investigate the relationships between high-touch event service quality, customer satisfaction, and e-WOM, as well as the mediating role of customer satisfaction. A quantitative research design was employed using survey data collected from 291 respondents who had attended high-touch events in Metro Manila. Data were analyzed using weighted mean, Pearson correlation, and mediation analysis. The results revealed that service quality has a strong positive relationship with customer satisfaction (r = 0.821, p < 0.05) and e-WOM (r = 0.835, p < 0.05). Customer satisfaction also significantly influences e-WOM (r = 0.786, p < 0.05) and partially mediates the relationship between service quality and e-WOM. These findings indicate that improving service quality in high-touch events enhances customer satisfaction, which in turn promotes positive e-WOM. The study highlights the importance of delivering high-quality interactive experiences to strengthen customer retention and engagement in the event industry.